MANNAN PRECIPITATION FROM ALOE VERA LEAF PULP JUICE USING METHANOL AND ISOPROPYL ALCOHOL AS ANTI-SOLVENT: EXPERIMENTAL AND EMPIRICAL MODELLING APPROACH - Diah Susetyo Retnowati; Andri Cahyo Kumoro (Reaktor, 2012)
Precipitation of mannan from Aloe vera leaf pulp juice was investigated using anti-solvent precipitation process under room temperature condition. The aims of this work were to study the effects of types (methanol and isopropyl alcohol) and amount of anti-solvent on the precipitation phenomena and to propose a simple mathematics model for evaluating the precipitation rate of mannan (Rβ). The experiments were carried out using a semi batch system; where continuous drop wise addition of anti-solvent to the Aloe vera leaf pulp juice was kept constant at 50.4 mL/min, while the speed of stirring was maintained at 675 rpm. At every run of the experiments, the time at which the precipitation began was recorded and the experiment was terminated when no further precipitation occurred. The samples were withdrawn from the system at every 25 min after the first precipitation for mannan analysis. The results of this work showed that isopropyl alcohol acted as a more effective anti-solvent to precipitate mannan from Aloe vera leaf pulp juice than methanol. The mathematics model represented the precipitation phenomena fairly well with average relative deviation only 11.73%, and finally suggested that the precipitation rate obeyed the zero order.  PENGENDAPAN MANNAN DARI JUS DAGING DAUN LIDAH BUAYA (ALOE VERA) MENGGUNAKAN METANOL DAN ISOPROPIL ALKOHOL SEBAGAI ANTI SOLVEN: PERCOBAAN DAN PEMODELAN DENGAN PENDEKATAN EMPIRIK. Pengendapan mannan dari jus daun lidah buaya (Aloe vera) dengan teknik pengendapan menggunakan anti-pelarut dikaji pada suhu kamar. Tujuan dari penelitian ini adalah untuk mempelajari pengaruh jenis anti-pelarut (metanol dan isopropil alkohol) dan massa anti-pelarut terhadap fenomena pengendapan mannan, serta mengembangkan model matematik dengan pendekatan empiric untuk mengevaluasi laju pengendapan mannan (Rβ). Percobaan dilakukan dalam sistem yang bekerja secara semi-batch, dengan anti-pelarut diumpankan secara terus menerus dalam bentuk tetesan-tetesan dengan laju 50,4 mL/men dan pengadukan dijaga tetap pada 675 putaran per menit (ppm). Pada setiap percobaan, waktu yang diperlukan sejak pengumpanan anti-pelarut hingga saat endapan pertama kali terbentuk dicatat, dan percobaan dihentikan jika tidak ada lagi endapan yang terbentuk. Cuplikan cairan diambil setiap 25 menit sejak endapan pertama terbentuk dan dianalisis kandungan mannannya. Hasil penelitian menunjukkan bahwa isopropil alkohol merupakan anti-pelarut yang lebih efisien dibandingkan dengan metanol untuk mengendapkan mannan dari jus daun lidah buaya. Dari pemodelan matematik diketahui bahwa laju pengendapan mannan mengikuti order nol. Model matematik yang diusulkan dapat mewakili fenomena pengendapan mannan dengan baik yang ditunjukkan dengan ralat rata-rata sebesar 11,73%.